Bone microstructure and atomic periodic disharmonization in osteoporosis - Zairin Noor; Mohammad Hidayat; Agus Hadian Rahim; Sutiman B. Sumitro (Universa Medicina, 2012)
Background Both cortical and cancellous bone display a complex, porous microstructure whose properties depend on the macrostructure of bone as well as age and health of the individual. The aim of this study was to compare the microstructure and characteristics of mineral atoms in osteoporotic and normal bone.